Rheological properties of sewage sludge during enhanced anaerobic digestion with microwave-H2O2 pretreatment. (1st July 2016) - Liu, Jibao; Yu, Dawei; Zhang, Jian; Yang, Min; Wang, Yawei; Wei, Yuansong; Tong, Juan
Abstract: The rheological behavior of sludge is of serious concern in anaerobic digestion. This study investigated the rheological properties of sewage sludge during enhanced anaerobic digestion with microwave-H2 O2 pretreatment (MW-H2 O2 ). The results showed that MW-H2 O2 pretreatment resulted in the improvement of sludge flowability and weakening of its viscoelastic properties. Further positive effects on the rheological properties of digested sludge during anaerobic digestion were observed. The flowability was improved with a low level of apparent viscosity. The decrease of the consistency index and increase of the flow behavior index indicated that the strength of the inner structures and non-Newtonian flow characteristics of digested sludge weakened. Both the storage modulus (G′) and loss modulus (G″) decreased, indicating that the viscoelastic behavior became weak. These effects were possibly attributed to the changes of the digested sludge micro-structures, such as extracellular polymeric substances (EPS). This study concluded that anaerobic digestion for treating sewage sludge combined with pretreatment is a more favorable option than single anaerobic digestion from the perspective of rheology. Graphical abstract: Highlights: Effects of MW-H2 O2 pretreatment on rheology of sludge through AD were studied. Pretreatment improved digested sludge flowability and reduced its elasticity. The variation of EPS possibly contributed to the rheology evolution of sludge. AD combined with pretreatment is a favorable option for treating sludge.